PENGENALAN ANALISIS STANDAR BELANJA SEBAGAI INSTRUMEN PENYUSUNAN ANGGARAN BERBASIS KINERJA: UPAYA PENINGKATAN KAPASITAS ANGGOTA DPRD KABUPATEN CILACAP DALAM PENYUSUNAN APBD - Alizar Isna (PARADIGMA: Jurnal Pengabdian Kepada Masyarakat, 2024)
One of the duties of DPRD members is to prepare and stipulate Regional Regulations (Perda) on the Regional Revenue and Expenditure Budget (APBD). In accordance with the laws and regulations that govern it, the preparation of the APBD is based on performance so that the preparation process must use the Standard Spending Analysis (ASB) as one of its instruments. In order for DPRD members to understand the concept of ASB and its function in preparing the budget, the material "Standard Spending Analysis (ASB) as an Instrument for Preparing a Performance-Based Budget" was discussed in the training which was packaged in the form of an Academic Study of the Draft Regional Regulation (Raperda) for the Regional Revenue and Expenditure Budget (APBD) of Cilacap Regency in 2024. The training used 2 learning methods, namely varied lectures and hypothetical situation techniques. Discussion of materials and discussions related to the problems of regional financial management in the era of regional autonomy and their relationship to the concept of performance-based budgeting and ASB, understanding ASB, legal basis for ASB, benefits and objectives of determining ASB, techniques for preparing ASB, examples of the results of preparing ASB for a district and its use when preparing an activity. and ASB adjustment techniques for the following year.